2019
DOI: 10.1186/s12902-019-0343-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glucose in screening for diabetes and pre-diabetes: how much is too much? Analysis of fasting plasma glucose and oral glucose tolerance test in Sri Lankans

Abstract: BackgroundFasting plasma glucose (FPG) is the most commonly used screening tool for diabetes in Sri Lanka. Cut-off values from American Diabetes Association recommendations are adopted in the absence of local data. We aimed to establish FPG cut offs for Sri Lankans to screen for diabetes and pre-diabetes.MethodsData on FPG and diabetes/pre-diabetes status were obtained from Sri Lanka Diabetes and Cardiovascular Study (SLDCS), a community based island wide observational study conducted in 2005–6. Sensitivity sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Studies conducted in Asian and Caucasian populations have revealed similar findings (6,19). One recent study was conducted to compare the sensitivity and specificity of FPG with OGTT in the diagnosis of pre-diabetes in the local setting and it showed FPG has low sensitivity to detect pre-diabetes similar to our findings (20). Use of OGTT or alternative screening tools such as glycosylated hemoglobin in addition to FPG to diagnose individuals with the pre-diabetes have been recommended to improve the diagnostic yield of pre-diabetes (5).…”
Section: Discussionsupporting
confidence: 89%
“…Studies conducted in Asian and Caucasian populations have revealed similar findings (6,19). One recent study was conducted to compare the sensitivity and specificity of FPG with OGTT in the diagnosis of pre-diabetes in the local setting and it showed FPG has low sensitivity to detect pre-diabetes similar to our findings (20). Use of OGTT or alternative screening tools such as glycosylated hemoglobin in addition to FPG to diagnose individuals with the pre-diabetes have been recommended to improve the diagnostic yield of pre-diabetes (5).…”
Section: Discussionsupporting
confidence: 89%
“…Diabetes can result in regulatory alterations in the hemostasis of calcium, phosphorus and magnesium ending with serious complications including cardiovascular disease and neurological disorders ( 7 , 8 ). According to the American Diabetes Association (ADA), pre-diabetes can be defined as either impairment of fasting glucose (5.6–6.9 mmol/L) or impairment of oral glucose tolerance test (2-h OGTT glucose 7.8–11.0 mmol/L) ( 9 ). Other studies showed that the pre-diabetic state is characterized by a reduction of glucose tolerance and delayed insulin secretion ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…HbA1c testing, which costs anywhere between USD22 and USD65 per test, is thus associated with a substantial opportunity cost and most public facilities in rural Sri Lanka lack the financial and human resource capacity to make HbA1c a sustainable marker of glycaemic control. 6 7 Since public subsidisation of diabetes focussed supplies and laboratory services are currently limited to a glucometer, monthly glucometer strips and a CBG measurement at regular appointments, CBG remains the most appropriate method of assessing glycaemic control in this population. Previous studies demonstrate significant concordance between HbA1c and CBG: both FPG and post-prandial blood glucose (PPBG) showed strong positive correlations with HbA1c in numerous clinical settings including Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%